PROFIL PENGETAHUAN CALON GURU SD TERHADAP LITERASI AKSARA LOKAL SASAMBO - Arif Widodo (Nurul Jadid University, 2020)
The literacy movement is not just a reading and writing activity, but also includes six basic literacies which include cultural literacy. The local script as part of local wisdom is one of the cultural heritage that should be preserved. This research is important to be carried out to determine the level of knowledge of prospective elementary school teachers of local characters, including the ability to read and write local characters. The results of this study are expected to be taken into consideration in the preparation of the PGSD curriculum, especially in developing local content curriculum. The subjects of this study were students of PGSD at the University of Mataram. The method used is a mixed method. Data collection through surveys and interviews. The instruments used were questionnaires and interview guidelines. Data are presented in tables and diagrams. Data analysis uses descriptive statistical techniques. Based on the results of the study it can be concluded that knowledge related to local literacy of elementary school teacher candidates is very low, with indicators of poor ability to read local scripts, write, copy, and only a few are able to mention local characters in sequence. The low literacy of local literacy elementary teacher candidates is exacerbated by the lack of literature owned and the low intensity of the use of local scripts. This causes motivation in learning local characters to be low because there is no practical use in daily life.